Allometric equations model for estimating an above and below ground biomass of dipterocarp forest in the tropics - I. Heriansyah; Luthfy Abdullah ,; J.S. Rahajoe; R. Susanti; Y. Lisnawati; Subarudi ,; R. Dewi; Darwo ,; Mawazin ,; Abdurachman ,; Karmilasanti ,; N. Wakhid; et al. (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Accurate measurement of carbon stocks is essential for assessing the forest carbon dynamics. One of carbon stocks measurement is an allometric equation that offer a cost-effective alternative for estimating tree biomass and carbon stocks by only measuring tree attributes, such as diameter and height of tree. Many allometric equations have been developed for estimating the forest biomass in tropical región. However, only few studies were found focusing on dipterocarp species, and most of them  applying allometric equations for aboveground biomass only. Objective of the study was to improve the accurate allometric equations for Dipterocarp Forest by developing its allometric equations of above-ground, root, and total biomass.METHODS: The study was conducted in tropical natural and planted forests in Indonesia (Sumatra, Java, and Kalimantan) and Peninsular Malaysia (Johor, Perak, and Pahang), with a total of eight plots at different provinces. All tree samples were collected using destructive analysis and categorized into living branches and twigs, dead branches and twigs, leaves and roots. A set of general equations for allometric model was developed to estimate tree volume and biomass. Then, the allometric equations were validated using validation models.FINDINGS: Generally, there are a positive relationship between tree diameter and height, tree volume and biomass. This study successfully developed several equations following the scenarios for above-ground, root-, and total- biomass using parameter diameter solely and a combination of tree diameter and height. Also, the validation of models against actual data showed that models for above-ground, root-, and total- biomass were not significantly different (probability value > 5 percent). Based on forest type, planted forests show more uniform relationships between tree diameter, height and biomass components, indicative of managed growing conditions. Whereas, natural forests exhibit greater variability, especially for larger trees, reflecting the heterogeneity of natural ecosystems.CONCLUSION: Allometric model for estimating biomass in dipterocarp forests was developed and validated using diameter and a combination of diameter and height as predictor variables. The models demonstrated a high coefficient of determination (> 90 percent), indicating strong predictive power for above-ground, root- and total biomass. Model 1 for above-ground biomass, Model 7 for root biomass, and Model 8 for total biomass were identified as the best-fitting models based on statistical significance and practical applicability.